2020
DOI: 10.3390/plants9101266
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Moderate and Severe Salinity on Composition and Physiology in the Biomass Crop Miscanthus × giganteus

Abstract: Saline land represents a growing resource that could be utilised for growing biomass crops, such as Miscanthus × giganteus (Greef et Deu.), for eliminating competition with staple food crops. However, the response mechanisms to different salinity regimes, in relation to the impact on quality of the harvested biomass and the combustion properties are largely unknown. Herein, the focus was on the salt-induced compositional changes of ion flux and compartmentalization in the rhizome, stems, and leaves in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 111 publications
(143 reference statements)
4
9
0
Order By: Relevance
“…Consistent with this, in our study, the effect of salinity on A n could be due to the change in g s (Figure 2) indicating stomatal limitation played a major role in affecting photosynthesis. Consistent with our results, a previous study in M. sinensis showed that both g s and A n first increased and then dropped with the duration and increase in salt stress (Sun et al, 2021). Likewise, it was also suggested in Stevia rebaudiana plants, a parallel change in g s and A n indicated that restriction of photosynthesis under salinity could be due to stomatal limitation (Hussin et al, 2017).…”
Section: The Interactive Effect Of High Co 2 and Salt Stress On Leaf ...supporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with this, in our study, the effect of salinity on A n could be due to the change in g s (Figure 2) indicating stomatal limitation played a major role in affecting photosynthesis. Consistent with our results, a previous study in M. sinensis showed that both g s and A n first increased and then dropped with the duration and increase in salt stress (Sun et al, 2021). Likewise, it was also suggested in Stevia rebaudiana plants, a parallel change in g s and A n indicated that restriction of photosynthesis under salinity could be due to stomatal limitation (Hussin et al, 2017).…”
Section: The Interactive Effect Of High Co 2 and Salt Stress On Leaf ...supporting
confidence: 92%
“…Moreover, due to peculiar leaf anatomy and greater CO 2 assimilation mechanisms, compared with C 3 plants, C 4 plants are generally relatively less influenced by salinity (Roy & Mathur, 2021). For example, previous studies have reported that both Miscanthus sinensis and Miscanthus × giganteus exhibited high level of salt tolerance, although they withstand different severity of the stress (Hung et al, 2009; Stavridou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which plants tolerate salinity stress are the following: (1) osmotic adjustment, (2) attenuation of salt concentration in the plant body through excretion (salt glands) and exclusion (from roots to leaves), and (3) preventing harmful effects on the plant body via compartmentalization [ 29 , 30 ]. A crop plant that maintains low Na + concentration and high dry weight biomass has more salinity tolerance than other populations [ 31 , 32 ]. The present study also reported salt excretion in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive ash content acquired shows an enormous diversity of mineral content [29]. The high ash content can be a result of the presence of salt inside the leaves [30] and the presence of varying amounts of minerals [28] due to the high salinity of seawater [31]. Seaweed has an excessive mineral content due to the fact it can absorb minerals from its environment.…”
Section: Discussionmentioning
confidence: 99%